Ventricular tachycardia mechanisms and prevention in patients with severe heart failure and left ventricular assist device. (3rd October 2022) - Hohendanner, F; Bock, M; Keznickl, J; Scholz, S; Potapov, E; Pieske, B; Gerds-Li, J H
Abstract:  : Terminal Heart Failure with reduced Ejection Fraction (HFrEF) is associated with severe morbidity and mortality. Mechanical Left Ventricular Assist Devices (LVAD) are often used to provide these patients with a last resort therapy and as bridge to transplant. However, HFrEF patients with LVAD have significant myocardial substrate for ventricular arrhythmias and the LVAD itself might be regarded as pro-arrhythmogenic. Aim of the current study was to investigate the mechanism of ventricular arrhythmias in LVAD patients and to provide evidence for the hypothesis that ad-hoc ablation/substrate modification during surgical LVAD implantation might reduce the risk of VT. We retrospectively analyzed invasive ablation procedures in patients with VT±LVAD and determined the mechanism of arrhythmia during electrophysiological examination (using 3D electroanatomical and local activation time mapping; Carto; Biosense Webster) in LVAD (n=17) and non-LVAD (n=12) subgroups. Mean age of the predominantly male (97%) patients was 60±2 years. VTs were directly LVAD associated (i.e. focal, adjacent to LVAD insertion or macro-reentry, around LVAD) in almost half of the LVAD patients. Number of radiofrequency ablation (RF) lesions and RF time were not significantly different between LVAD associated VT and non-LVAD associated VT patients. Within the LVAD patient group, freedom from VT (mean follow-up 40±6 months) was 50% upon ablation in patients with VTs originating from the LVAD region and 70% if ablation was conducted in non-LVAD regions. None of the LVAD associated and 22% of non-LVAD associated VT patients died during follow-up of these critically ill patients. Moreover, to reduce LVAD related arrhythmias and based on additional ex-vivo/in-silico derived data, we propose a distinctive (i.e. "star" shaped, LVAD encirclement) epicardial substrate modification during surgical LVAD implantation. In summary, a significant percentage of patients with LVAD exhibit LVAD-associated focal/macro-reentry VT and recurrence rates are high. VT likelihood is reduced ex-vivo/in-silico upon substrate modification targeting myocardium adjacent to a possible LVAD implantation site. Epicardial RF ablation during surgical LVAD implantation might allow prevention of LVAD-associated focal/macro-reentry VT. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): DFG